MAKING SENSE OF FEMALE STUDENTS FOR LEADERSHIP AT STAIN KUDUS: CHALLENGES AND OPPORTUNITIES - Sri Wahyuningsih (Marwah: Jurnal Perempuan, Agama dan Jender, 2019)
This paper explores the concepts, opportunities and challenges of female students leadership in STEC (STAIN English Club), STAIN Kudus. A qualitative study is conducted in this study. In order to gather data, in-depth interview and observation are conducted. The participants of interview are the head of STEC, the team and the members of STEC. The finding shows that the female leadership in STEC has not run well. Besides, there is a stereotype of negative judgment embedded to female leader. Therefore, this becomes a challenge for a female leader of STEC. In order to optimize the quality and performance leadership, the need of preparing qualified leaders is considerably crucial to improve STEC development. These include developing self-awareness among the leaders, the team and the members of STEC, creating a clear vision of the organization of STEC for future, developing strategic goals and innovative programs, developing cooperation and networking with other institutions